TROPHOBLASTIC DISEASE - Solidoro, Andrés (2015)
Between 1962 and 1980, the Departments of Gynecology and Medical Oncology INEN have handled 170 cases of trophoblastic disease. All patients had clinical and / or radiographic evidence and hormonal disease activity; histopathologic evidence was obtained when the disease was accessible to biopsy. Half of the patients are in the third decade of life, and a quarter in the fourth decade; 8 percent were under 20 years old. Only 27 percent of cases were under three months of sick time; in 21 percent of cases the disease duration was more than one year. 64.7% of cases had a history of mole, and 20 percent of abortion; in 10% of cases of history was normal delivery. Only 110 patients (64.75%) showed evidence of pelvic disease admission; 35% of 110 cases found evidence of disease in the pelvis. 55% of cases presented lung metastases, and 20% vulvovaginal metastasis; intestinal metastasis, liver or brain was 0.5 percent in 6 cases. 30 percent of patients had more than 100,000 IU of chorionic ganadotrofina in 24-hour urine, 29% was from 10,000 to 100,000 and 8.8% had less than 500 IU, the remaining 32 percent had between 500 and 10,000 IU. 29.4% (. 50 pts) had ETGNM, and 70 percent (120 cases) had E. Metastatic Gestational Trofobiástica; of these, 90 met high-risk criteria. Patients with nonmetastatic gestational trophoblastic disease, and low-risk metastatic disease were treated with Methotrexate single agent and / or Actinomycin D flashes; 100 percent of diseased the first group and 80 percent of the second group achieved complete regression of the disease. 50/90 patients were treated with ETGMAR onic agent (MTX or / and Act. D), 25 received sequential alternating QT, and 15 received no treatment, 20/50 (40%) of cells treated with agents and 11/25 (44%) of those treated with QT combined achieved CR. Sixty-three of the 170 patients are alive without evidence of disease for three or more years, and fifty-one sick without evidence of disease live for five or more years. Matástasis brain has the most ominous prognostic significance, since none of the 27 patients (15.88) presented that at some point in evolution, survived more than 6 months disease. Twenty of the cured patients presented one or more pregnancies carried to term and normal birth; none of the children born showed detectable abnormality.